Pengaruh Kejelasan Sasaran Anggaran dan Budget Emphasis Terhadap Senjangan Anggaran pada OPD Kabupaten Badung - Wibawa Putri, Ni Putu Achintya; Asri Dwija Putri, I G. A. M. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Local governments must account for the implementation of the Regional Revenue and Expenditure Budget (APBD), both in the form of financial statements and performance reports when viewed from financial measuring instruments in the form of budgets, there are still inaccuracies in determining inputs which ultimately do not indicate budget efficiency and effectiveness. The budget has a direct impact on a person's behavior which can lead to budgetary slack. This study aims to provide empirical evidence about the factors that influence budgetary slack in OPD of Badung Regency. This research was conducted at 28 OPD of Badung Regency. The number of samples was 110 respondents, which taken with purposive sampling technique. Based on the results of multiple linear regression analysis, it was found that budget goal clarity has no effect on budgetary slack and budget emphasis has a positive effect on budgetary slack. The results of this study provide information for the parties involved in preparing the budget when making decisions, determining policies in the future, while minimizing the